A review of waqf practices in the context of development in Malaysia / Ahmad Shazrin Mohamed Azmi, Noor Rosly Hanif and Siti Mashitoh Mahamood - Mohamed Azmi, Ahmad Shazrin; Hanif, Noor Rosly; Mahamood, Siti Mashitoh (Faculty of Architecture, Planning and Surveying, 2016)
The instrument of waqf is becoming as one of important welfare instruments in Islam due to its long lasting benefits. It is characterized by its Shariah principles and pillars as well as its governance bodies spelled out under the purview of Islamic laws and regulatory laws in the country. Commonly, waqf can be divided into waqf khas and waqf ‘am that require for different considerations mainly the extent of flexibility in determining the development intentions. Malaysia is gaining the effort to revitalize the waqf institution by focussing on at least five types of benefits namely as the religious, social welfare, health care, education, and economics. This article is intended to review the basic context of waqf and give some overviews on waqf development in Malaysia. In general, there is only one one-third of the total size of waqf lands in Malaysia are being developed, which left a huge opportunity to discover greater potentials from waqf institution in building up not only the socio benefits, but also the economics of the Muslims in the country. The involvement of the Federal Government in waqf development has spurred the use of waqf land into more dynamic intentions and bring out the economic opportunities. As a conclusion, this article is suggesting that waqf development in Malaysia is steadily in progress through the joint effort of various agencies and expected to see some greater contributions from waqf institution in the future.